Associations of circadian rest/activity rhythms with cognition in middle-aged and older adults: Demographic and genetic interactions - Rabinowitz, Jill A.; An, Yang; He, Linchen; Alfini, Alfonso J.; Zipunnikov, Vadim; Wu, Mark N.; Wanigatunga, Sarah K.; Schrack, Jennifer A.; Jackson, Chandra L.; Ferrucci, Luigi; Simonsick, Eleanor M.; Resnick, Susan M.; et al. (Frontiers in Neuroscience, 2022)
Objectives. Wrist actigraphs (accelerometers) can record motor activity over multiple days and nights. The resulting data can be used to quantify 24-hour activity profiles, known as circadian rest-activity rhythms (CRARs). Actigraphic CRARs have been tied to cognitive performance and decline in older adults; however, little is known about links between CRARs and performance or change in specific cognitive domains, or how individual differences may influence these associations. We investigated associations of actigraphic CRARs with cognitive performance and change in middle-aged and older adults, and explored whether age, sex/gender, race, and apolipoprotein E (APOE) e4 carrier status moderated these associations. Methods. Participants (N=422; 47% male) were cognitively healthy (i.e., without mild cognitive impairment or dementia) adults aged 50 years from the Baltimore Longitudinal Study of Aging who completed 5.6±0.8 nights of wrist actigraphy and tests of memory, executive function, attention, language, and visuospatial ability at the same visit the actigraph was issued; 285 participants had repeat cognitive testing 3.15 (1.29) years later. Predictors included indices of rhythm strength (i.e., amplitude; relative amplitude (RA); interdaily stability (IS); mesor), delayed timing of the rhythm peak (i.e., later acrophase; midpoint of an individual’s least active 5 hours (L5 time); midpoint of an individual’s most active 10 hours (M10 time), and fragmentation (i.e., intradaily variability (IV). Results. In main effects, later L5 time was cross sectionally associated with poorer memory, and greater IS predicted slower longitudinal memory decline. Later M10 time predicted greater declines in executive function. Associations of CRARs with cognition differed as a function of age, sex/gender, race, and APOE e4 carrier status. Conclusions. Among middle-aged and older adults, delayed circadian phase is associated with poorer cognitive performance and greater decline, and greater day-to-day rhythm stability is associated with better cognitive functioning and slower decline. Significant interactions suggest that CRARs are generally more strongly associated with cognitive performance and rate of cognitive decline among women, Black adults, older individuals, and APOE e4 carriers. Replication in independent samples is needed.